Hiperostosis ósea en defectos óseos críticos tratados con rhpth intermitente - Jammal, María Victoria (2012)
Recombinant Human Parathyroid Hormone (rhPTH 1-34) is an effective osteoporosis treatment. However, its effects on critical bone defects (CBD) are still unclear. The aim of this study was to assess morphological and tissues changes by systemic intermittent rhPTH administration for treatment of CBD. Forty three wistar female rat (body weight 150 ± 50 g) received CBD (5mm) on calvariae. The animals divided in 2 groups: A) Control Group (CG) received vehicle injection and B) Experimental Group (EG): received daily, rhPTH (20ug/kg/day) subcutaneous injection. Samples obtained from animals sacrificed at 1°, 3° and 6° weeks post surgery, were submitted for histological and histometrical studies. The bone formation on edges and CBD area did not regenerate defects. At 1° week, new bone showed basophilic cementales lines, arranged in a swirling pattern, resembling a disrupted mineralization. A focal osteoblasts hyperplasia was observed. At 3° and 6° weeks, there was a significant increase in bone thickness, many sutures were closed and endostic hyperostosis was observed. Large osteocytes showed granular and eosinophilic cytoplasm. Many showed bodies formation like ? Mallory-Denk?. New bone formed in EG exhibited at 1 week (0,84 % ± 0,6) and 3 weeks (0,42 % ± 0,1) compared with CG (0,21 % ± 0,07) and (0,65 % ± 0,2) respectively showing non significant statistical differences. At 6 weeks, EG shows significant bone formed (2, 81 % ± 0,6) compared with CG (1,06 % ± 0,2) (p= 0.023, Mann Whitney Test). Conclusion: rhPTH on calvariae CBD, increase Bone Multicellular Unit activities showing new bone formation on preexisting bone. Also, rhPTH 20ug induce non-neoplastic proliferative lesions.